A comprehensive strategy for transmission switching action in simultaneous clearing of energy and spinning reserve markets. (January 2015) - Aazami, Rahmat; Haghifam, Mahmoud Reza; Soltanian, Farzad; Moradkhani, Masoud
Highlights: Transmission switching strategy is incorporated in the stochastic joint energy and reserve markets. Proposed strategy considers AC constraints and stability criteria. A network reduction method and Benders decomposition algorithm are used speeding up the execution time. Proposed strategy is demonstrated on IEEE 14 and 57 bus systems. Abstract: There is a great resolution calling for smart grids in recent years. Introduction of new technologies, that make the network flexible and controllable, is a main part of smart grid concept and a key factor to its success. Transmission network as a part of system network has drawn less attention. Transmission switching as a new transmission service can release us from load shedding and remove the constraints' violations. Transmission switching can provide economic benefits compared to other control methods such as generation unit rescheduling or load shedding for contingency management. Utilizing a stochastic mix-integer nonlinear programming (SMINLP) model, transmission switching is used during contingencies and steady state to determine optimal required energy and reserve values. Stochastic joint energy and reserve markets with transmission switching considering dynamic constraints has been proposed to minimize the cost of supplying load, security expenses. Considering dynamic constraints in proposed model avoid the occurrence of transient instability when opening the line in transmission switching action. A network reduction method based on modified Jacobean AC Newton–Raphson technique power flow considering switchable line in technique is used for speeding up the calculation, efficiency and simplicity. To investigate the efficiency of the proposed strategy IEEE 14 bus test and IEEE 57 bus test system are studied. According to the obtained results, this strategy decreases energy and reserve marginal prices, as well as security cost.